The Controversy of Playing Metaverse Games for Preschoolers - Zulfa, Dina Jauharotuz; Putra, Yudithia Dian; Maningtyas, Rosyi Damayani Twinsari; Samawi, Ahmad (Universitas Negeri Malang, 2024)
This article provides an overview of the impact of playing metaverse games for pre-school children (4-6 years old), especially on their social and emotional development. Metaverse games are games played in a computer-generated world that is not real but user can see, experience, and interact as if they were in that world through a character called an avatar. We choose the metaverse games roblox, Minecraft, bus simulator, and Sakura school simulator, as well as social emotional development which focuses on interaction activities and expressing emotion. This focus was done based on literature review and children’s habits obtained when playing online games. This study used quantitative correlation method with saturated sampling method. The research was conducted on 36 children at RA Baipas Roudlotul Jannah through an instrument in the form of a questionnaire distributed to parents. Our article offers a different perspective on the social-emotional impact of gaming on pre-school children. Keywords: metaverse game, social emotional development, pre-school age children